High‐resolution evolution of terrigenous sediment yields in the Provence Basin during the last 6 Ma: relation with climate and tectonics. (25th January 2016) - Leroux, Estelle; Rabineau, Marina; Aslanian, Daniel; Gorini, Christian; Molliex, Stéphane; Bache, Francois; Robin, Cécile; Droz, Laurence; Moulin, Maryline; Poort, Jeffrey; Rubino, Jean‐Loup; Suc, Jean‐Pierre
Abstract: Basin‐wide correlation of Messinian units and Plio‐Quaternary chronostratigraphic markers (5.3 Ma, 2.6 Ma, 0.9 Ma and 0.45 Ma), the mapping of total sediment thickness and the determination of overall sedimentary volumes enabled us to provide a high‐resolution quantitative history of sediment volumes for the last 6 Ma along the Gulf of Lions margin. The results point to (i) a dramatic increase in terrigenous sediment input during the Messinian Salinity Crisis. This increased sedimentation reflects enhanced regional fluvial erosion related to the dramatic fall of Mediterranean base‐level. Stronger weathering due to a regional wetter climate probably also increased erosional fluxes. (ii) A sediment input three times higher during the Plio‐Quaternary compared to the Miocene seems in agreement with published measurements from World's ocean. However, the timing of this increase being uncertain, it implies that the trigger(s) also remain(s) uncertain. (iii) A decrease in detrital volume around 2.6 Ma is attributed to a regional change in the drainage pattern of rivers in the northwestern Alps. (iv) This study also highlights the Mid‐Pleistocene Revolution around 0.9 Ma, which resulted in an almost doubling of sediment input in the Provencal Basin.